Pulmonary hypofunction due to calcium carbonate nanomaterial exposure in occupational workers: a cross-sectional study. Issue 6 (3rd July 2018) - Li, Guoliang; Liang, Lihong; Yang, Jingchao; Zeng, Lihai; Xie, Zhiwei; Zhong, Yizhou; Ruan, Xiaolin; Dong, Ming; Yang, Zhanhong; Lai, Guanchao; Huang, Weixin; Yang, Aichu; et al.
Abstract: Calcium carbonate nanomaterials (nano-CaCO3 ) are widely used in both manufacturing and consumer products, but their potential health hazards remain unclear. The objective of this study was to survey workplace exposure levels and health effects of workers exposed to nano-CaCO3 . Personal and area sampling, as well as real-time and dust monitoring, were performed to characterize mass exposure, particle size distribution, and particle number exposure. A total of 56 workers (28 exposed workers and 28 unexposed controls) were studied in a cross-sectional study. They completed physical examinations, spirometry, and digital radiography. The results showed that the gravimetric nano-CaCO3 concentration was 5.264 ± 6.987 mg/m 3 (0.037–22.192 mg/m 3 ) at the workplace, and 3.577 ± 2.065 mg/m 3 (2.042–8.161 mg/m 3 ) in the breathing zone of the exposed workers. The particle number concentrations ranged from 8193 to 39 621 particles/cm 3 with a size range of 30–150 nm. The process of packing had the highest gravimetric and particle number concentrations. The particle number concentration positively correlated with gravimetric concentrations of nano-CaCO3 . The levels of hemoglobin, creatine phosphokinase (CK), lactate dehydrogenase, and high-density lipoprotein cholesterol (HDL-C) in the nano-CaCO3 exposure group increased significantly, but the white blood cell count (WBC), Complement 3 (C3), total protein (TP), uric acid, and creatinine (CREA) all decreased significantly. The prevalence rate of pulmonary hypofunction was significantly higher ( p = 0.037), and the levels of vital capacity (VC), forced vital capacity (FVC), forced expiratory volume in one second (FEV1), FEV1/FVC, peak expiratory flow and forced expiratory flow 25% (FEF 25%), FEF 25–75% were negatively correlated with gravimetric concentrations of nano-CaCO3 ( p < 0.05). Logistic analysis showed that nano-CaCO3 exposure level was associated with pulmonary hypofunction ( p = 0.005). Meanwhile, a dose-effect relationship was found between the accumulated gravimetric concentrations of nano-CaCO3 and the prevalence rate of pulmonary hypofunction ( p = 0.048). In conclusion, long-term and high-level nano-CaCO3 exposure can induce pulmonary hypofunction in workers. Thus, lung function examination is suggested for occupational populations with nano-CaCO3 exposure. Furthermore, future health protection efforts should focus on senior workers with accumulation effects of nano-CaCO3 exposure.